Interplay between swine enteric coronaviruses and host innate immune - Li, Mingwei; Guo, Longjun; Feng, Li (Frontiers in Veterinary Science, 2022)
Swine enteric coronavirus (SeCoV) causes acute diarrhea, vomiting, dehydration, and high mortality in neonatal piglets, causing severe losses worldwide. SeCoV includes the following four members: transmissible gastroenteritis virus (TGEV), porcine epidemic diarrhea virus (PEDV), porcine delta coronavirus (PDCoV), and swine acute diarrhea syndrome coronavirus (SADS-CoV). Clinically, mixed infections with several SeCoVs, which are more common in global farms, cause widespread infections. It is worth noting that PDCoV has a broader host range, suggesting the risk of PDCoV transmission across species, posing a serious threat to public health and global security. Studies have begun to focus on investigating the interaction between SeCoV and its host. Here, we summarize the effects of viral proteins on apoptosis, autophagy, and innate immunity induced by SeCoV, providing a theoretical basis for an in-depth understanding of the pathogenic mechanism of coronavirus.